MULTIDIMENSIONAL ANALYSIS OF DETERMINANTS IN THE IMPLEMENTATION OF THE FREE NUTRITIOUS FOODPROGRAM (MBG) ON REDUCING MALNUTRITIONPREVALENCE - Sutiyono; Wahyu Riniasih; Daviq Bagus Setiadi (LPPM Universitas An Nuur, 2026)
Background: Malnutrition remains a serious public health problem, both globally and nationally. As a strategic effort to address this issue, the Indonesian government launched the Free Nutritious Food Program (MBG) in 2025. The determinants of malnutrition are not limited to direct interventions such as food provision, but also encompass socioeconomic, environmental, and behavioral factors. Methodology: This study employed a descriptive correlational study conducted with a cross-sectional design. The sample was drawn from the population using stratified random sampling. Analysis was conducted by examining the frequency distribution, mean, and standard deviation to describe the characteristics of the respondents. Analysis using the Pearson Test and multivariate analysis using multiple linear regression to determine the simultaneous influence of determinants on malnutrition. Results: Statistical results showed that the following factors were associated with consumption patterns (r = 0.45; p = 0.001), parental income (r = 0.38; p = 0.003), parental education (r = 0.35; p = 0.005), environmental sanitation (r = 0.30; p = 0.010), MBG food quality (r = 0.52; p = 0.000), and MBG food distribution (r = 0.41; p = 0.002). Conclusion: The results of this study confirm that the MBG program has a positive impact on improving nutritional status, but its effectiveness is influenced by various multidimensional determinants. Program food quality is the most dominant factor, while socioeconomic and environmental factors continue to contribute significantly to the success of nutrition interventions.